Lacrimal Drainage System Obstruction Following Inferior Turbinate Surgery - Tachino, Hirohiko; Takakura, Hiromasa; Shojaku, Hideo; Fujisaka, Michiro; Fuchizawa, Chiharu; Hayashi, Atsushi (Frontiers in Surgery, 2020)
Objective: To provide information on the clinical characteristics and management of an uncommon acquired nasolacrimal drainage system obstruction (NLDSO). Methods: A patient was treated with microdebrider-assisted endoscopic marsupialization for a cystic lesion located in the synechiae between the inferior turbinate and the lateral wall of the inferior meatus. Results: A 21-year-old woman suffered from epiphora and purulent discharge 1 week after inferior turbinate surgery. Endoscopy reveled synechiae between the inferior turbinate and the lateral wall of the inferior meatus. Computed tomography-dacrocystography (CT-DCG) showed enlargement of the nasolacrimal duct and cystic accumulation of contrast medium from the lacrimal orifice posteriorly. The patient was treated with nasal endoscopic marsupialization of the cyst and then powered inferior turbinoplasty. Six months after the operation, both endoscopy and CT scan showed a widely patent left inferior meatus and nasolacrimal orifice. Conclusions: We report the first case of post-operative NLDSO following inferior turbinate surgery. Nasal endoscopy and CT-DCG are useful to diagnose the location of a NLDSO. Otorhinolaryngologists should be aware that surgery may lead to the formation of a NLDSO and that endoscopic marsupialization is a curative treatment for these distal-end NLDSO. NLDSOs are caused by synechiae, which are a complication of inferior turbinate surgery.